New specimens of Mourasuchus (Alligatoroidea, Caimaninae) from the Miocene of Brazil and Bolivia and their taxonomic and morphological implications. Issue 2 (3rd April 2019) - Cidade, Giovanne M.; Souza-Filho, Jonas P.; Hsiou, Annie Schmaltz; Brochu, Christopher A.; Riff, Douglas
Abstract : Cidade, G.M., Souza -Filho, J.P., Hsiou, A.S., Brochu, C.A., & Riff, D., 18 March 2019. New specimens of Mourasuchus (Alligatoroidea, Caimaninae) from the Miocene of Brazil and Bolivia and their taxonomic and anatomic implications. Alcheringa 43, 261–278. ISSN 0311-5518. Mourasuchus is one of the most peculiar crocodylians of all time, showing an unusual 'duck-faced' rostrum with thin, gracile mandibles. It includes four species restricted to the South American Miocene. Here, we describe ten late Miocene specimens of Mourasuchus, nine from the Solimões Formation of Brazil and one from Bolivia. All specimens are assigned to M. arendsi, but this assignment may change as the diversity and relationships within Mourasuchus are better understood. We also discuss several issues pertinent to the morphology of Mourasuchus : the presence of a braincase neomorph (the laterocaudal bridge), hypotheses about sexual dimorphism, the function of the squamosal 'horns' the presence of possible thermoregulatory functions in the genus. Additionally, the paleogeographic distribution of Mourasuchus in the Miocene of South America is also discussed. Giovanne M. Cidade* [giovannecidade@hotmail.com ], Universidade de São Paulo Campus de Ribeirao Preto, Biologia, Avenida Bandeirantes 3900, Ribeirao Preto, 14040-900, Brazil; Jonas P. Souza-filho [jpdesouzafilho@hotmail.com ], Universidade Federal do Acre, Departamento de Ciências da Natureza, Campus Universitário, UFAC, BR 364, Km 4, Distrito industrial, CEP 69915-900, Rio Branco, Acre, Brazil; Annie Schmaltz Hsiou [anniehsiou@ffclrp.usp.br ], Faculdade de Filosofia, Ciências e Letras de Ribeirão Preto, Universidade de São Paulo, Departamento de Biologia, Avenida dos Bandeirantes, 3900, Ribeirão Preto, 14040-901, Brazil; Christopher A. Brochu [chris-brochu@uiowa.edu ], University of Iowa, Iowa City, IA 52245, USA; Douglas Riff [driff2@gmail.com ], Universidade Federal de Uberlandia, Uberlandia, 38400902, Brazil.